A wideband array of stacked patch antennas using embedded air cavities in LTCC - Panther, A.; Petosa, A.; Stubbs, M.G.; Kautio, K. (IEEE microwave and wireless components letters, 2005)
An embedded air cavity in low temperature cofired ceramics (LTCC) is used to achieve a wideband response with stacked patch antennas. A single LTCC stacked patch antenna achieves a gain of better than 5dBi over an 18% bandwidth with a good impedance match. A 2/spl times/2 element array of stacked patches is also realized, and achieves a 3-dB gain bandwidth from 25 to 30GHz with a maximum gain of 11.1dBi.